Legal Consequences Of Using Power Of Attorney In Nominee Agreements: Flexibility And Legal Limitations - Najlalinka, Zahrafhia; Pujiyono, Pujiyono; Tuhana, Tuhana (CV. Inara, 2024)
The practice of nominee agreements involving the use of power of attorney has become an intriguing topic in the context of modern law. Nominee agreements refer to agreements entered into by certain parties, whereby one party cannot be the lawful owner of the ownership rights to an asset, particularly in the context of the participation of foreign nationals or among Indonesian citizens. However, this practice is also commonly employed by Indonesian citizens themselves, both in transactions between legal entities and individuals, as well as among individuals. Many of these practices are accompanied by formal resolutions through statements and power of attorney documents. This research aims to examine the legal consequences arising from such practices, as well as the extent to which they provide flexibility and the associated legal limitations.